2013
DOI: 10.12968/npre.2013.11.5.246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nurse prescribing in a community palliative care team

Abstract: Nurse independent prescribing (NIP) within adult community palliative care has been implemented in many areas ito improve the quality of care for these patients by providing a more flexible and streamlined service. In order to evaluate whether NIP does benefit community palliative patients, a small case study was carried out comparing how long it took for patients to receive their medication following assessment or review by the palliative care clinical nurse specialist (CNS), both before and after implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Although the aim of care is to review patients early in the lung cancer pathway (Roy Castle Lung Cancer Foundation 2013), patients with lung cancer are often given a life changing diagnosis with a short disease trajectory (McPhillips et al, 2015). This highlights the importance of an early assessment and identification of symptoms facilitated by the independent nurse prescriber when patients are in the terminal phase of their disease (Dawson 2013).…”
Section: Role Of Clinical Nurse Specialist As a Non-medical Prescribermentioning
confidence: 99%
See 1 more Smart Citation
“…Although the aim of care is to review patients early in the lung cancer pathway (Roy Castle Lung Cancer Foundation 2013), patients with lung cancer are often given a life changing diagnosis with a short disease trajectory (McPhillips et al, 2015). This highlights the importance of an early assessment and identification of symptoms facilitated by the independent nurse prescriber when patients are in the terminal phase of their disease (Dawson 2013).…”
Section: Role Of Clinical Nurse Specialist As a Non-medical Prescribermentioning
confidence: 99%
“…As the lung cancer trajectory progresses, patients' palliative care needs may change rapidly and will require meticulous monitoring of symptoms, which may include reviewing medications, especially for patients approaching the end of life. A case study carried out by Dawson (2013) described the effectiveness of independent nurse prescribing within a community palliative care team focussing on patients approaching end of life. The results suggested that patients had more timely access to medications when prescribed by the Clinical Nurse Specialist independent prescriber, than when prescribed by their General Practitioner/Family Physician.…”
Section: Role Of Clinical Nurse Specialist As a Non-medical Prescribermentioning
confidence: 99%
“…2 Patients may have a complex range of clinical issues related to their condition, and fluctuating symptoms, including severe pain, can be difficult to control, Review requiring frequent readjustment of medication. 3 The process of medicine access for symptom control can be a lengthy one, including obtaining a prescription for a medicine, ensuring it is dispensed correctly and supplied, together with information that enables patients and carers to manage medicines effectively in the home. Evidence from our previous studies suggests that for patients and carers receiving community-based palliative care, the experience of accessing medicines is often a considerable burden, involving multiple professionals and including a complex process of attaining and managing controlled drugs, such as opioids.…”
Section: Introductionmentioning
confidence: 99%